Dynamics and patterns of land levelling for agricultural reclamation of erosional badlands in Chambal Valley (Madhya Pradesh, India). Issue 2 (17th November 2017) - Marzolff, Irene; Pani, Padmini
Abstract: Gully and badland erosion constitute important land‐degradation processes with severe on‐site and off‐site effects above all in sedimentary deposits and alluvial soils of the arid and semi‐arid regions. Agricultural use of the affected land is impeded both by the irreversible loss of topsoil and the morphological dissection of the terrain. In various badland regions around the world, a solution to the latter problem is attempted by infilling of gullies and levelling of badland topography in order restore a morphology suitable for agricultural cultivation. Gully and badland levelling for agricultural reclamation has been conducted for decades in the large ravine lands of India. This study aims at analysing the distribution and dynamics of land levelling within the Chambal badlands in Morena district, Madhya Pradesh, between 1971 and 2015. Using high to medium resolution satellite images from the Corona, Landsat, Aster and RapidEye missions and a multi‐temporal classification approach, we have mapped and quantified areas that were newly levelled within eight observation periods. We analysed the spatial relation of levelled land to several physical and socio‐economic factors that potentially influence the choice of reclamation site by employing geographic information system (GIS) analysis methods and results from focus‐group discussions in selected villages. Results show that nearly 38 km 2 or 23% of the badlands in the study area have been levelled within 45 years. The levelling rate generally increases during the observation period, but the annual variability is high. We have found spatial relationships to badland morphology, vicinity of existing cropland and proximity to villages and drainage lines. From a socio‐economic point of view, availability of financial and technical means, access rights to the badland and ownership issues play an important role. Considering studies on soil degradation caused by levelling of badlands in other regions, the sustainability of the newly reclaimed fields in the Chambal badlands is questionable. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Gully and badland levelling for agricultural reclamation has been conducted for decades in the large ravine lands of India. Our study, which combines remote sensing and socio‐economic analysis, shows that 23% of an extensive part of the large Chambal Badlands of India has been levelled and reclaimed for agriculture within 45 years. The choice of levelling sites is influenced by physical and socio‐economic factors related, above all, to accessibility, and the sustainability of the reclaimed land is questionable.